Moving obsidian: The case of Antofagasta de la Sierra basin (Southern Argentinean Puna) during the late Middle and Late Holocene - Escola, Patricia Susana (2016)
This paper presents the results of an XRF analysis on the provenience of 118 obsidian artifacts from archaeological sites of the Antofagasta de la Sierra basin (Catamarca Province Argentina) dating to the late Middle and Late Holocene (c.4500–1100 BP). The time span considered encompasses a local process of gradual transformation from hunter-gatherer/early agro-pastoral groups to consolidated agro-pastoral societies. For this study, non-destructive elemental analysis of obsidian artifacts was conducted using two different X-ray fluorescence spectrometers (ED-XRF). This information was then supplemented by previous provenience results, undertaken on 59 obsidian archaeological artifacts from the same area. A comparative synthesis of chemical and macroscopic characterization of five obsidian sources located in Southern Argentinean Puna is also presented. The provenance of archaeological materials was assigned by comparison with twelve presently known Argentine sources. On this basis, late Middle and Late Holocene obsidian regional movement patterns, differential distribution and use of this raw material are discussed. Furthermore, this obsidian research lends support to the existence of exchange networks based on the use of different extra-regional obsidian sources located in the Northern Argentinean Puna.